Owner's Perception of Seizure Detection Devices in Idiopathic Epileptic Dogs - Bongers, Jos; Gutierrez-Quintana, Rodrigo; Stalin, Catherine Elizabeth (Frontiers in Veterinary Science, 2021)
Accurate knowledge of seizure frequency is key to optimizing treatment. New methods for detecting seizures are currently investigated in humans, which rely on changes in biomarkers, also called seizure detection devices. Critical to device development, is understanding user needs and requirements. No information on this subject has been published in veterinary medicine. Many dog health collars are currently on the market, but none has proved to be a promising seizure detector. An online survey was created and consisted of 27 open, closed, and scaled questions divided over two parts: part one focused on general questions related to signalment and seizure semiology, the second part focused specifically on the use of seizure detection devices. Two hundred and thirty-one participants caring for a dog with idiopathic epilepsy were included in the study. Open questions were coded using descriptive coding by two of the authors independently. Data was analyzed using descriptive statistics and binary logistic regression. Our results showed that the unpredictability of seizures plays a major part in the management of canine epilepsy and dog owners have a strong desire to know when a seizure occurs. Nearly all dog owners made changes in their daily life, mainly focusing on intensifying supervision. Owners believed seizure detection devices would improve their dog’s seizure management, including a better accuracy of seizure frequency and the ability to administer emergency drugs more readily. Owners that were already keeping track of their dog’s seizures were 4.2 times more likely to show confidence in using seizure detection devices to manage their pet’s seizures, highlighting the need for better monitoring systems. Our results show that there is a receptive market for wearable technology as a new management strategy in canine epilepsy and this topic should be further explored.